(untitled) - Blick, Andrew (Oxford, 2015)
This book, published at the time of the 800th anniversary of Magna Carta, considers a series of historical documents from Anglo-Saxon times onwards which sought to set out arrangements for the governance of England and later the UK as a whole
Keywords: Constitutional law,Luật hiến pháp; Great Britain,Vương quốc Anh